Nystagmus Parameters of Supine Roll Test Correlates With Prognosis After Repositioning Maneuver in Horizontal Semicircular Canal Benign Paroxysmal Positional Vertigo - Yu, Jia; Gu, Yongzhe; Meng, Guilin; Zhu, Xiaosa; Wang, Wenxie; Liu, Xueyuan; Jin, Aiping (Frontiers in Neurology, 2021)
Background: Positional nystagmus induced by supine roll test (SRT) is characteristic for diagnosing horizontal semicircular canal benign paroxysmal positional vertigo (HC-BPPV). In this study, we aim to explore the value of nystagmus parameters in SRT as prognostic factors in HC-BPPV. Methods: We retrospectively analyzed the nystagmus parameters of 813 patients diagnosed with HC-BPPV by SRT mode in the SRM-IV system through videonystagmograph. Then we used the computer-controlled canalith repositioning procedure (CCRP) mode for treatment. Based on the outcomes, patients were divided into either the cured group or the resistant group. The 1:1 propensity score matching (PSM) was applied to minimize potential selection bias. Then univariable and multivariable analyses were performed to identify the association of nystagmus parameters and the efficacy of CCRP. Results: Of the 813 patients, 99 (12.2%) were classified in the resistant group. The right side of HC-BPPV patients were twice the number of the left side patients (537 vs 276). PSM are used to pair resistant patients to the cured patients, in which 99 pairs were successfully matched. Results of univariate and multivariate analyses showed that patients in the resistant group have longer latency in the affected side (OR= 1.231 [1.110-1.366]; P<0.001) and slower slow phase velocity (SPV) in the healthy side (OR= 0.957 [0.917-0.999]; P=0.045). Conclusion: Nystagmus parameters may represent the characteristics of canalith. HC-BPPV patients with a longer latency in the affected side and slower SPV in the healthy side during SRT have a higher risk of HC-BPPV persisting after a single CCRP. Keywords: Benign paroxysmal positioning vertigo (BPPV); Horizontal semicircular canal; Supine roll test (SRT); Nystagmus parameters; Computer-controlled canalith repositioning procedure (CCRP); Prognostic factors